Symptom profile of postpartum and non-postpartum manic episodes in bipolar I disorder: a within-subjects study. (February 2020) - Gordon-Smith, Katherine; Perry, Amy; Di Florio, Arianna; Forty, Liz; Fraser, Christine; Casanova Dias, Marisa; Warne, Naomi; MacDonald, Tracey; Craddock, Nick; Jones, Lisa; Jones, Ian
Highlights: Symptom profiles of postpartum and non-postpartum manic episodes were compared. Within-subject design removed the potential effects of between-group heterogeneity. More mixed features with perplexity occurred during postpartum manic episodes. Childbirth may act as a pathoplastic trigger in women with bipolar disorder. Abstract: The relationship of postpartum mania to episodes of mania occurring outside the perinatal period among women with bipolar disorder remains controversial. Previous studies have used between-subjects designs to compare the clinical presentations of these episodes meaning the differences, in part, may reflect between-group differences. To overcome this we have undertaken within-subject comparisons of the symptom profile of postpartum and non-postpartum manic episodes in 50 women with DSM-IV bipolar I disorder. For each woman detailed symptom information on a postpartum episode of mania and a comparison non-postpartum manic episode was collected. The occurrence of manic, psychotic and depressive symptoms in these episodes were compared. Postpartum manic episodes had a significantly higher incidence of perplexity and excessive self-reproach. Classic manic symptoms, specifically pressured speech and increased sociability, were significantly less frequent in postpartum manic episodes. Overall there were significantly fewer manic symptoms and significantly more depressive symptoms in the postpartum episodes than in the non-postpartum episodes. The mixed presentation of postpartum manic episodes suggests childbirth may act as a pathoplastic trigger in women with bipolar disorder. The differences in symptom profiles suggests further research is warranted into whether differences in treatment response exist among women experiencing postpartum and non-postpartum manic episodes.